Conserved cysteine variants of metagenomic derived polygalacturonase concurrently shift its optima at acidic pH and enhanced thermostability: structural and functional analysis. Issue 1 (2nd January 2019) - Singh, Rajvinder; Kumar, Arbind; Chopra, Nisha; Mahajan, Ritu; Kaur, Jagdeep
Abstract : To study the effect of conserved cysteins on biochemical properties of a previously cloned metagenomic polygalacturonase (PecJKR01), single point variants A42C, M283C, and double variants M283C + F24C, M283C + A42C were constructed. Mutations resulted in shifting the pH toward lower range and enhanced thermostability. The mutants were optimally active at pH 5.0 as compared to pH 7.0 for wild type. Point variants demonstrated slightly higher enzyme activity at 60 o C than that of the wild type. In addition, the A42C/M283C + A42C variants displayed nearly 28–40% enhanced thermostability, while M283C + 24C was least thermostable among all variants/ wild type. Cys ( pKa 8.18) possibly interfered in the ionization state resulting in change in pH optima of variants. Structure function analysis suggested that the increased activity in A42C could be due to van der Waals interactions in S···Ar with Phe29 and formation of an additional hydrogen bond between Cys42-S....HN-Ala31. Higher thermostability and decreased enzymatic activity of M283C might be attributed to the incorporation of additional disulfide linkage between Cys283 S=S Cys255 and decreased cavity size. Overall cysteine at position 42 was most promising in shifting the optimum pH toward lower range as well as for thermostability of enzyme.